Research on the Theory of Procedural Justice in Civil Litigation Inclusiveness: From the Perspective of Civil Litigation and Diversified Dispute Resolution Mechanisms - Zhao, Guangyu (International Journal of Social Sciences and Public Administration, 2025)
The theory of procedural justice, which was transplanted to China in the 1990s, has undergone theoretical development and has had a profound impact on China's civil litigation procedures and judicial practices. However, it has also encountered challenges such as procedural instrumentalism and judicial centrism. The overall value orientation of our society is developing towards diversification, which has also led to the diversification of civil disputes and people's demand for justice in China. The theory of procedural justice in civil litigation not only needs to break the closed nature of research fields, but also needs to break the closed nature of justice theories in other fields. The inclusiveness of civil litigation procedures also requires the concept of sharing and co governance to resolve disputes. This article systematically constructs a program based on the theory of dialogue mechanism, aiming to open up channels for all forces that can assist in resolving civil disputes to enter the civil litigation process and help resolve disputes; On the other hand, based on the theory of open procedural justice, the connection and inclusiveness between civil litigation procedures and other dispute resolution mechanisms have been constructed at the theoretical and institutional levels, thus forming an inclusive theory of procedural justice.